An English Language Teacher's Pedagogical Response to Canada's Truth and Reconciliation Commission. (5th March 2019) - Walsh Marr, Jennifer
Abstract: This article describes the rationale and process of a content and language integrated learning initiative. An academic English instructor of international students reflects on the limitations and impact of critical language teaching materials drawing on texts about First Nations history and political activism in Canada on student learning in the program.